SHALLOW GEOLOGICAL STRUCTURES OF THE SOUTH SHETLAND TRENCH, ANTARCTIC PENINSULA - Loreto, Filomena M.; Della Vedova, Bruno; Accaino, Flavio; Tinivella, Umberta; Accettella, Daniela (Ofioliti, 2024)
In order to study the differential passive subduction among the three oceanic segments of the Phoenix Plate remnant, the R/V OGS-Explora acquired new geophysical data in the South Shetland Trench (offshore to the Antarctic Peninsula). An integrated geophysical dataset was acquired in the trench across the incoming oceanic plate segmented by the “D” and “E” oceanic Fracture Zones, and along the frontal part of the Antarctic Peninsula accretionary prism. We present here a high resolution multibeam bathymetry map, Chirp sub-bottom profiles and marine magnetic data to study changes in the deformational style along strike and to better understand features and processes of passive subduction. The new multibeam image and Chirp data display in detail shallow structures affecting the seafloor as a response to crustal deformation. Normal faults, bounding horst and graben structures cutting the incoming plate, are detected and characterized by variable orientation with respect to the inferred “D” and “E” Fracture Zones. Normal faults, width and depth of the trench and morphology of the frontal prism are related to bending and roll-back of the Phoenix Plate, and to inherited structural discontinuities. Some of these oblique faults offset the seafloor, with variable throws and with local dip changes. The orientation of the oblique faults, the different depth of the three oceanic segments and narrowing and deepening of the trench indicate that differential coupling between the Hero, Shackleton, “E” and “D” Fracture Zones may locally modify the regional stress field orientation and the sinking of each oceanic segment, during bending and roll-back.